Coseismic Deformation and Speculative Seismogenic Fault of the 2017 MS 6.6 Jinghe Earthquake, China, Derived From Sentinel-1 Data - Feng, Wei; Bai, Zechao; Ren, Jinwei; Huang, Shuaitang; Zhu, Lin (Frontiers in Earth Science, 2021)
A Ms 6.6 earthquake struck Jinghe County in Bortala Mongol Autonomous Prefecture of Xinjiang Uygur Autonomous Region on August 9, 2017. The earthquake occurred near the eastern part of the Kusongmuxieke Piedmont Fault (KPF) in the southwest of Junggar Basin. Using two pairs of coseismic SAR image data from the ascending and descending tracks from Sentinel-1 (European Space Agency), we processed the interferograms to obtain the coseismic deformation field. We calculate the fault slip distribution of the earthquake based on the elastic half-space rectangular dislocation model with the available location, geometry from seismic data and the coseismic deformation data. The results show that the earthquake deformation field has the typical characteristics of thrust faulting. The uplift deformation field is about 28 km long and 20 km wide. The maximum displacements of InSAR line-of-sight to the ascending and descending tracks are 49 mm and 68 mm, respectively. The main slip is concentrated at the depth of 10–20 km. The inverted seismic moment is equivalent to a moment magnitude Mw 6.3. This result is very similar to the slip distribution from the seismological inversion. The maximum deformation area and the distribution of aftershocks are both on the west side of the mainshock. They mutually confirm the characteristics of a unilateral rupture. According to stress triggering theory, the aftershocks within one month after the mainshock in the layer 10–14 km deep may have been triggered by the mainshock, and the transferred stress increases the seismic risk of the eastern section of the KPF fault. After more than one year, a Ms 5.4 earthquake occurred to the southwest of the MS 6.6 Jinghe earthquake. Beacause the stress drop change (<0.01 MPa) is too small for the Ms 5.4 earthquake to have been directly triggered. Based on the analysis of multisource data and the detailed geological investigation, the thrust Jinghenan fault which north of Kusongmuxieke Piedmont fault is inferred to be the seismogenic fault of the Ms 6.6 Jinghe earthquake.